Regulatory T cells (Tregs) monitoring in environmental diseases - Mićović, Vladimir (Array, 2009)
Abstract: The prevalence of environmental diseases is increasing worldwide and these diseases are an onerous burden both to the individual and to the public health. Urban air pollution is a grave problem in majority of metropolises, which contain high levels of traffic congestion generating great amounts of genotoxic substances. The contribution of such environmental exposure to increase prevalence of many allergic, environmental diseases and multiple chemical sensitivity or other related syndromes, as a result of an abnormal immune response based on environmental damage of lymphocyte subsets, is marked. Benzene is one of the most important air pollutants that are emitted by oil industry, since they are involved in almost every refinery process. Volatile organic compounds (VOCs) are a major group of air pollutants and play a crucial role in ecological damages, disturbing the ecosystem and human health. The variability of pollutants is an important factor in determining human exposure to these chemicals. The immune system possess a capacity to distinguish between innocuous and harmful foreign antigens and controls this action by mechanisms of central and peripheral tolerance, where crucial role play regulatory T cells (Tregs). We analyzed the characteristics of human Tregs of inhabitants living near gasoline industry which have assessed moderate spyrometric tests and compared them with those situated in rural areas. Our data demonstrate that the chronic inhalation exposure increases the percentage of Tregs cells, but contrary those of inhabitants with decreased spirometry values have shown diminished number of Tregs, which may contribute to the new therapeutic approach of environmental diseases